Civil Servant Payroll Accounting at The Office of Population and Civil Registration of Gunungsitoli City - Serniati Zebua; Zai, Kurniawan Sarototonafo; Dedi Irawan Zebua (CV. Doki Course and Training, 2025)
The objectives to be achieved in this study are to find out how payroll accounting is carried out at the Population and Civil Registration Office of Gunungsitoli City. The object of the study is the Population and Civil Registration Office of Gunungsitoli City. The population in this study is the Civil Servant Salary Report at the Population and Civil Registration Office of Gunungsitoli City. The sample in this study is the salary list and pay slips of Civil Servants (PNS) of the Population and Civil Registration Office of Gunungsitoli City in 2016. The data analysis technique uses a descriptive method. Based on the results of the study, the salaries of employees of the Population and Civil Registration Office of Gunungsitoli City are paid monthly, salaries are only given to legitimate employees who are appointed based on a letter of appointment and the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia. The Population and Civil Registration Office of Gunungsitoli City uses documents in payroll accounting consisting of attendance cards (attendance lists), salary lists, salary list recaps, salary account books, general cash books and cash disbursement books. The documents used in the Population and Civil Registration Office of Gunungsitoli City are almost the same as the theory that the researcher presents in the theoretical basis, but in the theoretical basis there are documents used, namely salary envelopes, but in the researcher's research, salary envelopes are no longer used due to the existence of salary account books for each employee.